Detection of Vancomycin Resistance among Enterococcus faecalis and Staphylococcus aureus - Rengaraj, Ramya (J Clin Diagn Res, 2016)
INTRODUCTION: Vancomycin remains the drug of choice for resistant gram positive infections caused by Enterococcus spp and Methicillin resistant Staphylococcus aureus (MRSA). Increased use of vancomycin has led to frank resistance and increase in MIC (MIC creep). Vancomycin intermediate Staphylococcus aureus (VISA), Vancomycin resistant Staphylococcus aureus (VRSA) & Vancomycin resistant Enterococci (VRE) are important emerging nosocomial pathogens resulting in treatment failures. AIM: This study was undertaken to detect vancomycin resistance among clinical isolates of Staphylococcus aureus and Enterococcus faecalis by phenotypic and genotypic methods. MATERIALS AND METHODS: The study was conducted in a 1850 bedded university teaching hospital from November 2013 to April 2014. Non-repetitive, consecutive clinically significant Staphylococcus aureus (109) and Enterococcus faecalis (124) were included in this study. They were identified up to species level by conventional and automated methods. Susceptibility to various antibiotics was tested by disc diffusion method. MIC of vancomycin was determined by agar dilution method. Inducible resistance to clindamycin was detected by the D test. Methicillin resistance in Staphylococcus aureus (MRSA) was screened using cefoxitin disc. All isolates were subjected to polymerase chain reaction (PCR) to detect van A and van B genes. RESULTS: Out of 109 Staphylococcus aureus isolates, 54 were MRSA. By MIC there was no resistance observed to vancomycin.MIC(50) was 1μg/ml. None of the isolates harboured van A and van B. Among Enterococcus faecalis, sixteen isolates (12.9%) and four isolates (3.2%) exhibited resistance to vancomycin and teicoplanin by disc diffusion respectively. All isolates were susceptible to linezolid. Van A was detected in 2, van B in 7 and one had both van A and van B. CONCLUSION: PCR remains the gold standard for diagnosis of vancomycin resistance. There was no resistance observed to vancomycin among Staphylococci though the MIC creep detected is a cause for concern. Eight percent of Enterococci were vancomycin resistant.